2014
DOI: 10.4236/ajps.2014.513208
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential F<sub>1</sub> Hybrids in Maize Responsive to Water Deficient Condition

Abstract: The assessment of heterotic F1 combinations is a basic requisite for hybrid seed development. A set of 30 F1 hybrids along with their parental inbred lines were evaluated under both normal and water deficit conditions for various physiological and agronomic traits. Highly significant mean squares due to general combining ability, specific combining ability and reciprocal effect were observed for all traits under both water regimes. Components of variation exhibited greater estimates for GCA variance (б 2 g) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
2
7
1
1
Order By: Relevance
“…Both general (GCA) and specific (SCA) combining abilities mean squares were found to be highly significant for all studied traits, indicating the importance of both additive and non-additive genetic variances in determining the performance of these traits. These results are in line with those of Abdel- Moneam (2005), Abdel- Moneam et al, (2009), Sultan et al (2011), Attia et al (2013), Sultan et al (2013), Abdel- Moneam et al (2014) and Wattoo et al (2014).…”
Section: -Analysis Of Variancesupporting
confidence: 90%
See 1 more Smart Citation
“…Both general (GCA) and specific (SCA) combining abilities mean squares were found to be highly significant for all studied traits, indicating the importance of both additive and non-additive genetic variances in determining the performance of these traits. These results are in line with those of Abdel- Moneam (2005), Abdel- Moneam et al, (2009), Sultan et al (2011), Attia et al (2013), Sultan et al (2013), Abdel- Moneam et al (2014) and Wattoo et al (2014).…”
Section: -Analysis Of Variancesupporting
confidence: 90%
“…Both general and specific combining ability variances were highly significant for almost all the characters, except anthesis-silking interval. Wattoo et al (2014) reported that highly significant mean squares due to general combining ability, specific combining ability and reciprocal effects were observed for all traits under both water regimes. Components of variation exhibited greater estimates for GCA variance (б 2 g) than SCA variance (б 2 s) for majority of the traits under both normal and stress conditions depicting the predominant role of additive genetic component.…”
Section: Introductionmentioning
confidence: 98%
“…For this reason, the analysis was performed with 8 parents. It was also decided not to use reciprocal hybrids because normally, there are no reciprocal effects for grain yield traits under well-irrigated [17,21] and water-stress conditions [11,22].…”
Section: Methodsmentioning
confidence: 99%
“…Aminu et al (2014), Okasha, et al (2014), Umar et al (2014) and Al-Naggar et al (2016) revealed that both additive and non-additive gene actions were responsible for the control of grain yield under water stress and non-stress conditions, but the magnitude of dominance was much higher than additive variance for this trait. On the other hand, additive and additive × additive types of gene action were greater importance in the inheritance of number of rows/ear (Al-Naggar et al, 2016); plant height, days to 50% silking, anthesis-silking interval (ASI), grain yield and 100-Kernel weight (Wattoo et al 2014).…”
Section: Analysis Of Variancementioning
confidence: 99%
“…If both GCA and SCA variances are non-significant indicate that epistatic gene effects play role for studying characters. Various studies have been made on combining ability under drought stress in maize viz EL-Hosary et al (2013) Alamerew and Warsi (2014), Aminu et al (2014), Okasha et al (2014), Umar et al (2014), Wattoo et al (2014), Erdal et al (2015), Al-Naggar el al. (2016), Matin et al (2016), andSaif-ul-Malook et al (2016).…”
Section: Introductionmentioning
confidence: 99%